2010
DOI: 10.1177/0146167210390523
|View full text |Cite
|
Sign up to set email alerts
|

Planning What Not to Eat: Ironic Effects of Implementation Intentions Negating Unhealthy Habits

Abstract: The present studies tested the effectiveness of implementation intentions with an "if [situation], then not [habitual response]" structure. Based on ironic process theory and the literature on the processing of negations, it was expected that these "negation implementation intentions" would, ironically, strengthen the habit (situation-response association) one aims to break. In line with the hypotheses, forming negation implementation intentions resulted in cognitive ironic rebound effects as well as behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 31 publications
(72 reference statements)
2
50
0
3
Order By: Relevance
“…Implementation intentions have been shown to be effective in promoting diverse health behaviors, including eating a low-fat diet, limiting binge drinking, completing cancer screenings, and increasing exercise (for a meta-analysis across many behavioral domains, see Gollwitzer & Sheeran, 2006), although very few of those findings come from patient populations. It should also be noted that implementation intentions to not engage in a behavior (e.g., "If I think about the tempting chocolate, I will not eat it") have not been found to be effective (Adriaanse, Van Oosten, De Ridder, De Wit, & Evers, 2011). Specifying what "not" to do appears to backfire by making the temptation behavior salient, thereby making it more desirable and more difficult to control.…”
Section: Strategy 2: Automating Behaviormentioning
confidence: 99%
“…Implementation intentions have been shown to be effective in promoting diverse health behaviors, including eating a low-fat diet, limiting binge drinking, completing cancer screenings, and increasing exercise (for a meta-analysis across many behavioral domains, see Gollwitzer & Sheeran, 2006), although very few of those findings come from patient populations. It should also be noted that implementation intentions to not engage in a behavior (e.g., "If I think about the tempting chocolate, I will not eat it") have not been found to be effective (Adriaanse, Van Oosten, De Ridder, De Wit, & Evers, 2011). Specifying what "not" to do appears to backfire by making the temptation behavior salient, thereby making it more desirable and more difficult to control.…”
Section: Strategy 2: Automating Behaviormentioning
confidence: 99%
“…In some cases, planning is found to have a harmful effect for goal striving (e.g., Adriaanse et al 2011;Bayuk, Janiszewski, and LeBoeuf 2010;Dalton and Spiller 2012). Joining the recent literature, in this research we further probe the effect of planning by examining the role played by two basic variables in goal pursuit, namely, goal distance and concrete implementation plans.…”
mentioning
confidence: 96%
“…A number of mechanisms are involved in such negative effects, including specific plan formats, inplan versus out-of-plan actions, the individual's current construal level, and the number of goals considered. For example, recent studies showed that when implementation intentions are stated in an "if, then not to do" structure, the behavior to be avoided ironically becomes more likely, due to its greater accessibility (Adriaanse et al 2011). Other research found that concrete planning decreased one's ability to act on goal-consistent, out-of-plan opportunities (Bayuk et al 2010).…”
mentioning
confidence: 99%
“…"), or focus on ignoring the critical cue (" … , then I'll ignore her request!"). Recent research (Adriaanse, Van Oosten, De Ridder, De Wit, & Evers, 2011) suggests that negation implementation intentions are less effective than the latter two types of implementation intentions (i.e., replacement and ignore implementation intentions). However, an important alternative way of using implementation intentions to protect one's ongoing goal striving from derailment exists.…”
Section: Implementation Intentions As a Means To Overcomementioning
confidence: 99%